The Southeastern Librarian, Vol.43, No.01 and No.02, Spring and Summer 1993 - Johnson, Theresa; Preuit, Catherine (The Southeastern Library Association, 1993)
The Southeastern Librarian, Vol.43, No.01 and No.02, Spring/Summer 1993. Periodical.
1 electronic record. 43 pages. Scanned from original document. Contents Include - SELA OFFICERS and Staff - front cover, State Library Association Officers - cover back, President's Page - 3, Editor's Page - 4. ARTICLES and FEATURES - John Cotton Dana Award Winners by Kathleen Imhoff - 6, Telephone Reference Training: Some Suggestions and Observations by Daniel R. Smith - 7, Publication Requirements For Academic Librarians by Sharon Lee Stewart - 11, Ecuadorians in Tennessee: A Cultural Encounter by Joel A. Stowers - 14. DEPARTMENTS - People - 16, Bulletin Board - 22, New & Useful - 24, Stateside View - 27, Calendar - 36. SELA ASSOCIATION - Guidelines for SELn Submissions - 2, New Members - 18, Reports from State Reps - 26, Biennium Plans - 32, State Editors - 37, Membership Form - 39.
Keywords: Periodicals | Southeastern Library Association